Management of English Language Learning Process for Children and Adolescent through Distance Learning Program at Homeschooling - Musdalifah Ifah Rahman (MAJESTY JOURNAL, 2020)
The research aimed to illustrate how distance learning programs can be organized or administered at "Primagama Course Place" in Makassar. This study combined qualitative development with the design of the case study. For this study, the writer has used several measures to collect data: interviews, observations, and documents. With the credibility, transferability, reliability, and confirming ability the validity of the information was checked. The final results of the study indicated that the students were planning the online classes, learning sources, information technology, and developing the curriculum. The most recent study findings showed that online preparation was developed, sources were studied, information technology and curriculums design were developed; students were able to understand the online programs and other books through their IT; distance learning framework was introduced by the day-to-day newspaper and parent control; programs evaluated.